Circulating Endothelial Progenitor Cells Decrease in Infants with Bronchopulmonary Dysplasia and Increase after Inhaled Nitric Oxide - Qi, Yuanyuan (Public Library of Science, 2013)
BACKGROUND: Impairment of endothelial progenitor cells (EPCs) has been shown to contribute to the development of bronchopulmonary dysplasia (BPD). In the current study, the relationship between EPC changes of after birth and the development of BPD was investigated, and the effects of inhaled nitric oxide (iNO) on EPCs were evaluated. METHODS: Sixty infants with a gestational age of less than 32 weeks and a birth weight of less than 1500 g were studied. NO was administered to infants who were receiving mechanical ventilation or CPAP for at least 2 days between the ages of 7 and 21 days. EPC level was determined by flow cytometry at birth, 7, 21 and 28 days of age and 36 weeks’ postmenstrual age (PMA), before and after the iNO treatment. Plasma concentrations of vascular endothelial growth factor (VEGF), stromal cell-derived factor-1 and granulocyte-macrophage colony-stimulating factor were determined via immunochemical assay. RESULTS: Twenty-five neonates developed BPD, 35 neonates survived and did not develop BPD. EPC level was decreased on day 7 and 21 in infants who later developed BPD compared with infants that did not develop BPD. From birth to 21 days of age, BPD infants had a persistently lower VEGF concentration compared with non-BPD infants. No difference was found between the two groups at day 28 or 36 weeks PMA. In infants that later developed BPD, iNO raised the KDR(+)CD133(+) and CD34(+)KDR(+)CD133(+) EPC numbers along with increasing the level of plasma VEGF. CONCLUSION: EPC level was reduced at 7 days of age in infants with BPD, and iNO increased the EPC number along with increasing the level of VEGF. Further studies are needed to elucidate the mechanism leading to the decrease of EPCs in infants with BPD and to investigate the role of iNO treatment in the prevention of BPD.